Quality Confirmation Tests for Power Transformer Insulation Systems - Vahidi, Behrooz; Teymouri, Ashkan (Springer International Publishing : Imprint: Springer, 2019)
This book focuses on oil-paper insulation included in power transformers, especially for EHV and UHV transformers. The importance on insulation ever increased due to a growing voltage rating of transformers. Within the last decades, although research on the transformer insulation and diagnosis methods has advanced a lot, the insulation of HV transformers remained more or less unchanged. The book is divided into five chapters; the first and second chapters explain the basics of oil insulation, while the third chapter focuses on paper insulation. The final two chapters deal with the methods and outcome of testing both techniques. The primary target audience for this book is graduate students and power system engineers.